Correlating multimode strain and electrode configurations for high-performance gradient-index phononic crystal-based piezoelectric energy harvesting. Issue 1 (2nd November 2022) - Kim, Dae-Su; Choi, Wonjae; Kim, Sun-Woo; Kim, Eun-Ji; Nahm, Sahn; Kim, Miso
Abstract : A pattern electrode design suitable for a gradient-index phononic crystal-based piezoelectric energy harvesting system is derived from multimode strain analysis, yielding an unprecedented power output of 7.1 mW in elastic wave energy harvesting. Abstract : A gradient-index phononic crystal (GRIN PnC) capable of manipulating wave propagation can serve as an excellent input wave energy focusing platform for amplifying energy harvesting power generation. However, despite its remarkable focusing capability, the finite wavelength of the propagating elastic waves in the focal area causes voltage cancellation inside a piezoelectric element under multimode strains having opposite directions; this limits the capacity of the GRIN PnC-based energy harvesting system. This study demonstrates a rational electrode configuration for a piezoelectric energy harvesting (PEH) device that can maximize the performance of a given GRIN PnC platform. The multimode strain analysis experimentally performed on the PEHs distributed over the focusing area confirms that the patterned electrode PEH configuration is the most effective in alleviating strain and voltage cancellation while efficiently transferring the focused elastic wave energy. Furthermore, a proper combination of electrical connections between the patterned electrodes substantially increases the piezoelectric potential across the ceramic by maximizing the strain difference. The simultaneous tailoring of the piezoelectric ceramic composition and the electrode configuration leads to a maximum power generation of 7.06 mW even under off-resonance conditions, the largest ever reported in elastic wave energy harvesting.